A Case-Control Study: The Impact of Unintentional Discrepancies and Pharmacist Discharge Prescription Review on 30-Day Hospital Readmission. (June 2020) - Elbeddini, Ali; Yang, Lucy; Aly, Ahmed
Introduction: Medication discrepancies on hospital discharge are common and occur despite the use of technology to generate electronically created discharge (e-discharge) prescriptions, justifying pharmacist involvement. No published studies have focused on medication discrepancies as a risk factor for readmission. The aim was to explore the relationship between medication discrepancies on discharge and readmission rates, and how both are affected by pharmacist intervention.Objectives: The primary objective was to establish the relationship between medication discrepancies on the e-discharge prescription and hospital readmissions within 30 days of discharge. Secondary objectives were to determine the 30-day readmission rate with and without pharmacist involvement, and risk factors for 30-day readmission.Methods: This was a matched case-control study where cases and controls consisted of patients readmitted and not readmitted to hospital within 30 days of discharge from the general medicine service, respectively. Case patients were defined as patients who had been readmitted to the hospital within 30 days of discharge from the general medicine unit. Control patients were defined as patients who had not been readmitted to the hospital within 30 days of discharge. Chi-square statistics was used to analyze the association between the presence of medication discrepancy at discharge and 30-day readmission. Multivariate logistic regression was used to further analyze the associations to determine which risk factors best relate to 30-day readmission.Results: Between January 1, 2017 and December 31, 2017, a total of 401 e-discharge prescriptions were reviewed, and 194 cases were readmitted within 30 days of discharge. Similar proportions of patients were readmitted compared with not readmitted regardless of whether discrepancies were identified on the e-discharge prescriptions, and there was no relationship identified between medication discrepancies and readmission within 30 days (odds ratio [OR] = 1.04; P = .854). The readmission rate with and without pharmacist involvement was similar between the case group (50%) and control group (48.0%). The proportion of discharge prescriptions with discrepancies was 48.8% in the group that had pharmacist involvement and 47.0% in the group that had no pharmacist involvement. Additionally, a LACE score of 12 or greater was identified as a statistically significant risk factor for readmission (OR = 2.13; P < .001).Conclusions: Pharmacist review of the e-discharge prescription did not affect the readmission rate. A LACE score of 12 or greater was associated with a higher risk of readmission. Future studies are needed to identify patient groups at high risk of readmission and to determine pharmacist interventions that could reduce readmission rates.